Evolution of the generalized body of knowledge on project management - Kononenko, Igor Vladimirovich; Lutsenko, Svitlana Yuryevna (НТУ "ХПИ", 2018)
An analysis of the literature on the creation and application of hybrid project management methodologies on the basis of fully plan-driven and Agile methodologies is made. It is shown that every year the volume of application of methodologies, which combines the advantages of fully plan-driven and Agile approaches is growing. To create a special methodology for a particular project, a generalized body of knowledge on project management can be used. The task is to complement the generalized body of knowledge on project management components of popular Agile methodologies DSDM and FDD. Currently, the generalized body of knowledge includes the components of PMBOK Guide, the ISO21500 standard, the PRINCE2 methodology, the SWEBOK Guide, agile methodologies Scrum, XP, and Kanban. The structure of the generalized body of knowledge on project management is given. DSDM principles and FDD values are added to it. The DSDM principles fall into three groups: values and principles relating to the interaction of team members, values and principles relating to the product of the project, and values and principles relating to the project team working technology. The values of FDD are only in the last group. The life cycles, roles, and responsibilities of these methodologies are described. The concept of a process for DSDM is proposed. The process in DSDM is actually the project life cycle. Other processes in DSDM are not provided. DSDM uses the concept of Products. The analysis showed that for this framework, the concepts of processes can be introduced. The creation of each DSDM product requires an appropriate process. As a result of the DSDM analysis, a set of processes was proposed. The proposed DSDM processes and FDD operations are inserted into the knowledge areas and process groups table of the generalized body of knowledge on project management. The DSDM and FDD practices have been added to the knowledge base.

Сделан анализ литературы по вопросам создания и применения гибридных методологий управления проектами на основе плановых и Agile методологий. Поставлена задача дополнения обобщенного свода знаний по управлению проектами компонентами популярных Agile методологий DSDM и FDD. Приведена структура обобщенного свода знаний по управлению проектами. В него добавлены принципы DSDM и ценности FDD, жизненные циклы, роли и ответственности этих методологий. Принципы DSDM попали в три группы: ценности и принципы, касающиеся взаимодействия членов команды, ценности и принципы, относящиеся к продукту проекта, ценности и принципы, касающиеся технологии работы команды проекта. Ценности FDD попали только в последнюю группу. Процессы DSDM и операции FDD вставлены в таблицу областей знаний и групп процессов обобщенного свода знаний по управлению проектами. В свод знаний добавлены практики DSDM и FDD.
Развитие обобщенного свода знаний по управлению проектами
Keywords: плановые методологии; принципы; жизненные циклы; fully plan-driven methodologies; Agile methodologies; principles; life cycles